Strengthening the Character of the Nation through the Social Movement of Zikir - Tanjung, Rahmy Fuady; Ariawan, Sandy (IJECA (International Journal of Education and Curriculum Application), 2022)
This research aims to prove the benefits of zikir that contribute positively to the strengthening of the character of the nation. The approach used in this research was qualitative, and data collection used interview, observation, and documentation techniques, with 6 informants involved in it. Data validity assurance technique was conducted by extending the time of data collection, persistence of observation, data triangulation, and conducting negative case analysis. The results of this study were: (1) The concept of social thoughts in building social movements and to be implemented in the civilization based on three things, namely: social of right society (الصفحة في المتواحدة االمة), social of law society (القانونية في المتواحدة االمة) and social gathering of philosophy (الفالسفية في المتواحدة االمة); (2) Forms of activities developed in their social movements through theological thinking based on social movements, including recitation, Tahlilan, Zikir Akbar and Haul Majelis Zikir; (3) The inhibiting and supporting factors of the theological thought movement and the social movement of thought in building the social movement, which are the clear management and the congregation that are Istiqomah in participating in the activities